Improving learning achievement of Civics material on the function of Pancasila as an adhesive for national unity by using the discovery method - Erfandi (PPPM STKIP PGRI Lamongan, 2022)
The purpose of this study is to increase the level of students' understanding of the function of Pancasila which is the theme of learning through classroom action research. The subjects in this study were 7th graders at SDN Balongwangi III, Tikung District, Lamongan Regency. The author's consideration of taking the research subject is that fifth grade students can increase the motivation and achievement of Civics learning with the Discovery learning method. The results of the study found that the use of the discovery learning method was able to improve Civics learning abilities. By using the discovery method, Civics learning outcomes increased from the average in cycle 1 which was only 69, in cycle 2 to 85. This increase in learning outcomes was obtained after students were directly involved in the process of finding problems presented by the teacher. This hands-on experience makes students enthusiastic about learning.